Effect of game addiction on reactive-proactive aggression in adolescents (Annals of Medical Research, 2021)
Aim: Rapid advances in technology cause children to become acquainted with technological products at an earlier age. Today’s children and adolescents, called the Generation Z, use digital technology effectively. Video game addiction can affect mental health in the next generation of children and adolescents and lead to aggressive behavior. The aim of this study was to identify the effect of game addiction on reactive proactive aggression in secondary education students. Material and Methods: The data of the research, which was patterned by the relational screening method, was collected from secondary education students who attended high schools in Malatya city center. The sample group consists of 192 secondary education students who were randomly selected from within the population. The data of the study was collected through “The Game Addiction Scale for adolescents” and “Reactive-Proactive Aggression Scale (RPAS)”. Independent Groups t test, ANOVA and Linear Regression Analysis were used in the analysis of the data. Results: The study found that gender has a significant effect on reactive proactive aggression. Aggression levels of male adolescents were significantly higher than females. Aggression levels of adolescents in the 10th grade were found to be higher than those of the adolescents in the other grades.Conclusion: According to the research results, game addiction accounts for 53% reactive-proactive aggression.
Keywords: Adolescent; game addiction; reactive-proactive aggression